Phyllanthus niruri leaf extract and its mediated silver nanoparticles as anticancer agent against neuroblastoma cancer (SH-SY5Y) cell lines - Zakaria, Nur Shuhada Binti; Khor, Boon-Keat; Rosdi, Nur Azimah Binti; Bakar, Nurul Ashikin Binti Abu; Johari, Nurul Farah Anis Binti; Francis, Lifi; Murugaiyah, Vikneswaran; Arumugam, Thangamani; Raja, Pandian Bothi (Journal of Phytology, 2025)
Silver nanoparticles (AgNPs) have enormous potential in numerous medical uses, such as molecular imaging, drug delivery, and treatment of different diseases, including cancer. Among many AgNP syntheses, the eco-friendly production of AgNPs utilising plants has many advantages including, sustainable and inexpensive process. Further, it provides safer and more effective treatment of numerous diseases. In this research, Phyllanthus niruri (PN) leaf extract was utilised for the biological synthesis of AgNPs. UV-Vis spectroscopy, ATR-FTIR spectroscopy, FESEM-EDX, and TEM were applied to analyse the synthesised P. niruri - mediated silver nanoparticles (PN-AgNPs). The images from FESEM and TEM analysis show the AgNPs are in spherical shapes with surface sizes of 11 to 63 nm and 12 to 24 nm, respectively. The EDX spectrum indicates that the nanoparticles contain 88.46% silver. PN and PN-AgNPs were further investigated to see whether they have any anticancer properties against the SH-SY5Y neuroblastoma cell line. Both PN and PN-AgNPs were effective in killing cancer cells, but the results indicated that PN-AgNPs had higher cytotoxic effects than PN.